Comparing textbook outcomes among patients undergoing surgery for cancer at U. S. News & World Report ranked hospitals. Issue 6 (2nd March 2020) - Mehta, Rittal; Tsilimigras, Diamantis I.; Paredes, Anghela Z.; Sahara, Kota; Moro, Amika; Farooq, Ayesha; White, Susan; Ejaz, Aslam; Tsung, Allan; Dillhoff, Mary; Cloyd, Jordan M.; Pawlik, Timothy M.
Abstract: Background: The objective of the current study was to define and compare rates of textbook outcomes (TO) among patients undergoing colorectal, lung, esophagus, liver, and pancreatic surgery for cancer at U.S. News & World Report (USNWR) ranked hospitals. Methods: Medicare Inpatient Standard Analytic Files 2013‐2015 were utilized to examine the relationship of TO and USNWR hospital ratings following surgery for colorectal, lung, esophageal, pancreatic, and liver cancer. TO was defined as no postoperative surgical complications, no prolonged length of hospital stay, no readmission within 90 days after discharge, and no postoperative mortality within 90 days after surgery. Results: Among the 35, 352 Medicare patients included in the cohort, 16, 820 (47.6%) underwent surgery at honor roll hospitals, whereas 18 532 (52.4%) underwent surgery at non‐honor roll hospitals. The overall proportion of patients who achieved TO was 50.1%. In examining the clinical outcomes of patients who underwent surgery, there was no difference in the odds of achieving TO at honor roll vs non‐honor roll hospitals (colorectal: odds ratio [OR], 0.87; 95% confidence interval [CI], 0.69‐1.10; lung: OR, 1.07; 95% CI, 0.87‐1.32; esophagus: OR, 1.44; 95% CI, 0.72‐2.89; liver: OR, 1.27; 95% CI, 0.87‐1.84; pancreas: OR, 1.04; 95% CI, 0.67‐1.62). Conclusion and Relevance: Patients undergoing surgery for lung, esophageal, liver, pancreatic, and colorectal cancer had comparable rates of TO at honor roll vs non‐honor roll hospitals. No linear association was observed between hospital position in the rank and postoperative outcomes such as TO indicating that patients should not overly focus on the exact position within USNWR ranked hospitals. These data highlight to patients and physicians that up to one‐half of patients undergoing surgery for cancer should anticipate at least one adverse outcome.